Knowledge and Practice Regarding Menstrual Hygiene among School Going Adolescents of Sulaimani city - Karem, Nassreen Ahmad; Mahmood, Avin Ali; Amin, Bekhal Abdalwahid (Journal of Neonatal Surgery, 2025)
Background and Objectives: Menstrual hygiene (MH) is a crucial aspect of adolescent health, impacting both physical and mental well-being. This study aimed to evaluate MH knowledge and practices among school-aged adolescents in Sulaimani City, Iraq. Methods: A cross-sectional study was conducted between January and March 2025, involving 195 female students aged 12–16 years from three randomly selected private schools. Participants were chosen through a two-stage random sampling process. Data were collected using a structured, pre-tested questionnaire covering sociodemographic information, menstrual history, knowledge about menstruation, and hygiene practices. Results: Among 195 adolescent girls (mean age: 13.78 ± 0.911 years), 61% (n=119) began menstruation at 12–13 years. Prior menstrual knowledge was reported by 59% (n=115), with mothers as the primary source (52.8%, n=103). Initial reactions included fear (31.3%, n=61) and embarrassment (39%, n=76). Hygiene practices: 66.7% (n=130) knew to change pads every 4 hours, and 90.3% (n=176) emphasized handwashing. Menstrual discomfort affected 72.3% (n=141) in class, with 63.6% (n=124) reporting academic impacts. Age, maternal education, employment, and household economics influenced hygiene practices. Conclusion: The knowledge and understanding of various menstrual aspects among the girls were moderate, with nearly 50% demonstrating adequate understanding of menstruation. Their practices and behaviors related to MH were generally satisfactory. Menstruation and its associated processes negatively impacted the comfort and participation of many adolescents in school and educational activities.